Repair of paraesophageal hiatal Hernias-is a fundoplication needed?: a randomized controlled pilot trial - Müller, Beat P.; Achtstätter, Lena Verena; Diener, Markus K.; Büchler, Markus W.; Linke, Georg R. (Journal of the American College of Surgeons, 2015)
Background - The need for a fundoplication during repair of paraesophageal hiatal hernias (PEH) remains unclear. Prevention of gastroesophageal reflux represents a trade-off against the risk of fundoplication-related side effects. The aim of this trial was to compare laparoscopic mesh-augmented hiatoplasty with simple cardiophrenicopexy (LMAH-C) with laparoscopic mesh-augmented hiatoplasty with fundoplication (LMAH-F) in patients with PEH. - Study Design - The study was designed as a patient- and assessor-blinded randomized controlled pilot trial, registration number: DRKS00004492 (www.germanctr.de/). Patients with symptomatic PEH were eligible and assigned by central randomization to LMAH-C or LMAH-F. Endpoints were postoperative gastroesophageal reflux, complications, and quality of life 12 months postoperatively. - Results - Forty patients (9 male, 31 female) were randomized. Patients were well matched for baseline characteristics. At 3 months, the DeMeester score was higher after LMAH-C compared with LMAH-F (40.9 ± 39.9 vs. 9.6 ± 17; p = 0.048). At 12 months, the reflux syndrome score was higher after LMAH-C compared with LMAH-F (1.9 ± 1.2 vs. 1.1 ± 0.4; p = 0.020). In 53% of LMAH-C patients and 17% of LMAH-F patients, postoperative esophagitis was present (p = 0.026). Values of dysphagia (2.1 ± 1.6 vs 1.9 ± 1.4; p = 0.737), gas bloating (2.6 ± 1.4 vs 2.8 ± 1.4; p = 0.782), and quality of life (116.0 ± 16.2 vs 115.9 ± 15.8; p = 0.992) were similar. Relevant postoperative complications occurred in 4 (10%) patients and did not differ between the groups. - Conclusions - Laparoscopic repair of PEH should be combined with a fundoplication to avoid postoperative gastroesophageal reflux and resulting esophagitis. Fundoplication-related side effects do not appear to be clinically relevant. Multicenter randomized trials are required to confirm these findings.